Etnoconhecimento de professores e moradores sobre fauna silvestre na RDS do Tupé - Sarmiento, Jose Damian Ortiz (2023)
The central aim of this study is to understand the relationships that can be established by teachers who teach Science and Geography, between the scientific knowledge taught in the classroom and the traditional knowledge of residents about wildlife. The research was carried out in two schools in the Tupé community, the Canaã II Municipal School and the Paulo Freire Municipal School, both belonging to the Tupé Sustainable Development Reserve. Four teachers from each school and ten residents from each community took part. This is a qualitative, phenomenological study. Data collection techniques such as interviews and focus groups were used. Moraes and Galiazzi's (2016) Textual Discourse Analysis (TDA) technique was used to analyze the data. During the research, it was found that teachers have limited knowledge of the reserve's wildlife. Residents, on the other hand, demonstrated that they had extensive traditional knowledge of the local fauna. This difference in knowledge made it possible to establish a dialog between the residents and the teachers, so that the latter could relate scientific and traditional knowledge in the teaching of Science and Geography. The results of the research indicate the need for ongoing training processes for teachers, addressing issues related to education for sustainability and local wildlife, in order to guide teaching processes. In addition, it is important to emphasize the importance of including the residents' traditional knowledge in the classroom, in order to value and perpetuate it. Keywords: Scientific knowledge. Traditional knowledge. Education for sustainability. Science teaching. Geography teaching.